The Influence of Workload and Work Environment on Employee Performance: Pengaruh Beban kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan - Tumonglo, Delvia; Purwanto, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The purpose of this study was to analyze the effect of workload and work environment partially and simultaneously on employee performance at PT. Thena Ely Sejahtera, South Tangerang City. The results of this study are expected to be the basis for policy making in human resource management, especially in increasing employee productivity and welfare. This research is included in the explanatory quantitative category, namely research that aims to explain the causal relationship between variables through hypothesis testing. This approach is used to determine the effect of workload and work environment on employee performance. The subjects of the study were all employees of PT. Thena Ely Sejahtera in South Tangerang City, totaling 43 people. The total sampling technique was used, with the number of respondents actively filling out the questionnaire as many as 30 people. Data were collected through closed questionnaires compiled using a Likert scale of 1–5. The questionnaire was distributed online using digital communication media to reach all respondents efficiently. The data were analyzed using multiple linear regression analysis to determine the simultaneous and partial effects of workload and work environment on employee performance. The analysis process was carried out with the help of the SPSS version 25 program, and was preceded by descriptive statistical analysis. This study shows that workload and work environment have a significant effect on employee performance at PT. Thena Ely Sejahtera. Partially, workload has a positive effect with a significance value of 0.015, while the work environment has a dominant and significant effect with a significance value of 0.000. Simultaneously, both variables explain 69.8% of the variation in employee performance. This confirms that proper workload division and the creation of a conducive work environment are very important to increase productivity